Relation between pathomorphological response in tumors after neoadjuvant chemotherapy and clinico-morphological and molecular prognostic factors in patients with breast cancer - Timovska, Yu.O.; Pivnyuk, V.M.; Oliynichenko, G.P.; Anikushko, M.F.; Zachartseva, L.M.; Chekhun, V.F. (Experimental Oncology, 2009)
To determine the correlation between tumor pathomorphological response (PMR) after neoadjuvant chemotherapy (NACT) and clinico-morphological and molecular prognostic factors in patients with breast cancer (BC), and to determine the possible impact of the PMR and estrogen receptors (ER), progesterone receptors (PR) and Her-2/neu BC status on the disease course. Methods: The data from the medical history of patients on IIB stage (T2N1M0, T3N0M0) (n = 247), who received treatment with NACT, were used. The correlation between the parameters was determined using the Spearman’s coefficient. Patient’s survival was analyzed by Kaplan – Meier method. The association between PMR grades with the risk of disease relapse was estimated by Cox’s regression analysis. Results: PMR grade correlated with tumor differentiation grade (rho = 0.38; p 0.05) and BC subtypes (rho = 0.05; p > 0.05). The patients with the same PMR grades didn’t differ by the number of lymph node metastases (p > 0.05) and differed by the presence of embolus in tumor vessels (p < 0.05). The rates of 3-years disease-free survival (DFS) differed between the groups of patients with different PMR grade (χ2 = 25.5; p < 0.0001). The patients with the grade 2–3 of pR had highest survival (p < 0.05). The groups of patients with identical subtype of BC had different survival rates dependent on PMR grades (for basal subtype (χ2 = 15.176; p < 0.001); luminal A subtype (χ2 = 14.9; p 0.05). The risk of disease relapse depended on PMR grade: for grade 2–3 it was significantly decreased (HR = 0.71, 95% CI — 0.25–2.9, p = 0.0037), and for grade 4–5 it was the highest (HR = –1.23, 95% CI — 0.24–5.05, P = 0.0001), while 0–1 grade had no impact on the risk of disease relapse (HR = 0.22, 95% CI 0.08–0.38; p = 0.7). Conclusion: The data of combined clinical, histological and immunohistochemical analysis have shown that PMR grades may serve as the criteria for individualization of adjuvant treatment of the patients with locally advanced BC.